Shore, Megan, Religion and conflict resolution: Christianity and South Africa’s Truth and Reconciliation Commission - Muhammed Haron (Acta Theologica)
From text: “Religion and conflict resolution,” as field of study, may be viewed as a relatively new area of specialization in contemporary international studies and more specifically in political studies. This may be attributed to the fact that religion has made a dramatic comeback into the public arena after decades of marginalization, and that it has gradually played a positive role in developmental affairs internationally. In the light of these developments, Megan Shore – who is a staff at the University of Western Ontario in Canada – decidedly paid attention to this area by giving particular attention to the way Christianity influenced the South African Truth and Reconciliation Commission (TRC) and the general outcomes in this postconflict nation-state.